Expanding the Role of Nurses to Improve Hypertension Care and Control Globally - Cheryl R. Dennison Himmelfarb; Yvonne Commodore-Mensah; Martha N. Hill (Ubiquity Press, 2016)
The role of the nurse in improving hypertension control has expanded over the past 50 years, complementing and supplementing that of the physician. Nurses' involvement began with measuring and monitoring blood pressure (BP) and patient education and has expanded to become one of the most effective strategies to improve BP control. Today the roles of nurses and nurse practitioners (NPs) in hypertension management involve all aspects of care, including (1) detection, referral, and follow up; (2) diagnostics and medication management; (3) patient education, counseling, and skill building; (4) coordination of care; (5) clinic or office management; (6) population health management; and (7) performance measurement and quality improvement. The patient-centered, multidisciplinary team is a key feature of effective care models that have been found to improve care processes and control rates. In addition to their clinical roles, nurses lead clinic and community-based research to improve the hypertension quality gap and ethnic disparities by holistically examining social, cultural, economic, and behavioral determinants of hypertension outcomes and designing culturally sensitive interventions to address these determinants.